2003
DOI: 10.1007/s00068-003-1284-6
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Effect of Tumor Necrosis Factor Alpha on Wound Angiogenesis and Epithelialization

Abstract: Background: The role of tumor necrosis factor alpha (TNF-␣) in wound healing is unclear and the results are contradictory. In vivo, TNF-␣ induces vessel growth, an important step in promoting wound healing. However, a reduced amount of collagen, hydroxyproline, and granulation tissue was found after TNF-␣ treatment. It is also unknown if this is a direct effect, by influencing cells involved in wound healing, or an indirect effect due to a negative or positive effect on cells such as macrophages. Material and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…TNF-α at the wound site directly or indirectly, stimulates fibroblast proliferation, promotes re-epithelialization and neo-vascularization, and enhances wound breaking strength. This supports our findings that decreased TNF-α in the wound of septic animals might be a cause for impaired wound healing [18], [19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…TNF-α at the wound site directly or indirectly, stimulates fibroblast proliferation, promotes re-epithelialization and neo-vascularization, and enhances wound breaking strength. This supports our findings that decreased TNF-α in the wound of septic animals might be a cause for impaired wound healing [18], [19].…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that local elevation of TNF-α expression is able to enhance wound repair while depletion of TNF-α has the opposite effect [18]. TNF-α at the wound site directly or indirectly, stimulates fibroblast proliferation, promotes re-epithelialization and neo-vascularization, and enhances wound breaking strength.…”
Section: Discussionmentioning
confidence: 99%
“…The role of TNFα in wound healing is still unclear. It is known to induce angiogenesis, an important step in the promoting wound healing but reduces the amount of collagen deposition . Thus, it can be concluded that the accelerated wound healing of PCAg1 treated sample is predominantly through the upregulation of IL10 and TGFβ1 and the downregulation of IL1β.…”
Section: Resultsmentioning
confidence: 97%
“…injection of mice with carrageenan (CGN -a lysosomedisrupting and phagocyte-damaging compound) (Frank et al 2003) 24 hours before single WBI resulted in the almost total abrogation of the synthesis of NO in the collected peritoneal Mφ regardless of whether the cells were obtained from the irradiated or sham-exposed mice , Nowosielska et al 2006b, 2008). This finding supports a possible involvement of NO in the Mφ-mediated anti-tumor effect of the low-level exposures to X-rays.…”
Section: E M Nowosielska and Othersmentioning
confidence: 99%